AN OVERVIEW OF LANGUAGE POLICY IN FRANCE - Nikolovski, Zoran (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
The purpose of this paper is to provide an overview of the language policy in France in relation to French and the regional languages. We start the overview from the Renaissance period when the French national feeling began to form and the distinctiveness of the French nation started to manifest, leading to increased usage of the French language and gradual superseding of the regional languages. Taking into consideration the fact that after the French Revolution in 1789, the unity policy of the French nation intensifies and thus the directions of action in the languages of its territory change, we divided the overview of the language policy in France in two parts: before and after the Revolution. For the revolutionaries, the ignorance of the French language was an obstacle for the democracy and spreading the revolutionary ideas, thus extending the superseding of the regional languages throughout the 19th and early 20th century. After the World War II, the regional languages and cultures received more attention and they were regarded as a treasure that needed to be preserved and their disappearance to be prevented. According to the relations and the language activities undertaken by France in the contemporary period, we distinguish Language policy in relation to the French language and Language policy in relation to the regional languages.